Smart farming: disease detection in crops - Balram, G; Kiran Kumar, K (International Journal of Engineering and Technology, 2018)
Automation in the market has been for decades now in the market. These systems run all through the day but there has not been any design which regards to identifying and classifying objects in specific and giving apt solution to them. Latest technologies like image processing and advanced machine learning mechanisms have become the core of the science and innovations. Our projectâ€™s idea is a broad concept that integrates various subjects and generates solutions to energy saving, cooling, automation and structural design. Â To get the desired results, above are the few constraints which play a major role in yielding high productivity from the crops. And besides them, the classification of objects through image processing and machine learning is used instead of the man power to accomplish the target to reduce the amount of hardware used